1994
DOI: 10.1152/ajpgi.1994.267.6.g1035
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine-enriched enteral diet increases splanchnic blood flow in the rat

Abstract: The hemodynamic consequences of glutamine (Gln)-enriched nutrition have not been investigated. This study investigates the effects of a Gln-enriched enteral diet on organ blood flows and systemic hemodynamics. Male Fischer 344 rats (n = 24) were randomized to a group that received a 12.5% (wt/wt) Gln-enriched enteral diet or an isonitrogenous isocaloric control diet for 14 days. Blood flow measurements were performed at day 16 using 46Sc-labeled microspheres. In the Gln-enriched group, higher organ blood flows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 0 publications
0
15
1
1
Order By: Relevance
“…Glutamine is a unique amino acid in many respects: it is the most abundant free amino acid in the blood, it provides energy from muscle and adipose tissue for the gut, it allows for nontoxic, interorgan transport of ammonia [35], and it promotes gut mucosal growth and barrier function [36]. In fact, intravascular glutamine might protect against total parenteral nutrition-associated intestinal atrophy [36] and enterocolitis while improving splanchnic blood flow [37]. Additionally, glutamine might provide protection to the gastrointestinal tract in pathologic conditions such as peptic and duodenal ulcers, ileitis, and enteropathies associated with malnutrition [32 for review].…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine is a unique amino acid in many respects: it is the most abundant free amino acid in the blood, it provides energy from muscle and adipose tissue for the gut, it allows for nontoxic, interorgan transport of ammonia [35], and it promotes gut mucosal growth and barrier function [36]. In fact, intravascular glutamine might protect against total parenteral nutrition-associated intestinal atrophy [36] and enterocolitis while improving splanchnic blood flow [37]. Additionally, glutamine might provide protection to the gastrointestinal tract in pathologic conditions such as peptic and duodenal ulcers, ileitis, and enteropathies associated with malnutrition [32 for review].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal immaturity and poor perfusion are eminent risk factors for necrotizing enterocolitis in premature neonates. In contrast to an earlier experimental study [23], Mercier et al [24] reported no benefits of enteral glutamine on mesenteric blood flow (assessed by Doppler ultrasound) in 21 healthy premature neonates (27-35 weeks of gestational age). Another randomized trial in healthy term infants aimed at investigating the effect of the supplementation of nucleotides on postprandial mesenteric blood flow.…”
Section: Macronutrients and Gastrointestinal Blood Flow In Normal Conmentioning
confidence: 79%
“…11 Immediately after the microsphere procedure, the abdomen was opened and blood samples (0.4 mL) were drawn from the left renal vein, the hepatic vein, the portal vein, and aorta as earlier described in detail. 6 F were computed according to the "reference organ" technique. 14 Portal venous flow was computed as the sum of the arterial flows through the splanchnic organs (ie, the stomach, pancreas, spleen, small intestine, and colon).…”
Section: Hemodynamic Measurements and Blood Samplingmentioning
confidence: 99%